Successful Treatment of Hair Loss and Restoration of Natural Hair Color in Patient with Alopecia Areata Due to Psychological Disorder Using Exosomes: Case Report with 6-Month Follow-Up - Emanuel Barbosa Bento; Cláudia Matos; Howard Lopes Ribeiro Junior (Cosmetics)
Alopecia areata (AA) is an autoimmune disorder causing non-scarring hair loss, which is often triggered by psychological stress. Conventional treatments, such as corticosteroids and immunotherapy, show variable efficacy and can cause side effects like hair discoloration. Exosome therapy, utilizing extracellular vesicles, presents a promising alternative, though its use in stress-related AA remains underexplored. A 39-year-old male with unifocal AA on the right parietal scalp developed hair loss following emotional distress after his fiancée’s death. Methotrexate and prednisolone were ineffective, prompting a bioregenerative approach using rose stem cell-derived exosomes (RSCEs) combined with thulium laser therapy. Six monthly sessions of RSCEs (20 mg/vial, 10 billion exosomes) were administered, with laser pre-treatment enhancing absorption. Within one month, vellus hair regrowth appeared, progressing to an increased density and pigmentation at three months. By six months, complete regrowth and natural pigmentation were achieved, with reduced inflammation confirmed by trichoscopy. The therapy was well-tolerated, with no adverse effects. This case highlights RSCE therapy as a promising treatment for stress-induced AA, achieving significant regrowth without corticosteroid-related side effects. Further studies are needed to validate its efficacy and refine protocols for broader clinical applications.